THE RELATIONSHIP BETWEEN QUARTER-LIFE CRISIS AND SUBJECTIVE WELL-BEING IN EARLY ADULT STUDENTS OF THE FACULTY OF PSYCHOLOGY AT UNIVERSITAS PRIMA INDONESIA - Anggi Elisa Rahmi; Amelia; Mentari A.P.T. Sijabat; Haposan Lumbantoruan; Achmad Irvan Dwi Putra (RADJA PUBLIKA, 2026)
Abstract Early adulthood is a transitional period in an individual’s life that is often accompanied by the phenomenon of the quarter-life crisis. During this phase, individuals frequently experience confusion in determining life direction, academic pressures, and uncertainty about the future. Such situations can affect the level of subjective well-being among students, which relates to life satisfaction as well as positive and negative emotional experiences.This study was conducted to examine the relationship between quarter-life crisis and subjective well-being among early adult students at the Faculty of Psychology, Universitas Prima Indonesia. The study employed a quantitative correlational design. The sample consisted of 100 students for the instrument trial and 200 students for the main study, selected using purposive sampling. Data were collected using Likert scales to measure levels of quarter-life crisis and subjective well-being.The research instruments demonstrated excellent reliability, with Cronbach’s Alpha scores of 0.950 for the quarter-life crisis scale and 0.927 for the subjective well-being scale. Data analysis techniques included descriptive statistics and the Pearson Product-Moment correlation test. The analysis revealed a significant negative relationship between the two variables, with a correlation coefficient of r = −0.693 and a significance level of p < 0.001. This finding indicates that higher levels of quarter-life crisis among students tend to be associated with lower levels of subjective well-being. Overall, the results suggest that the relationship between these two variables is strong.